2003
DOI: 10.1063/1.1615679
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle-assisted microwave absorption by single-wall carbon nanotubes

Abstract: Irradiance influence on the multicolor photochromism of mesoporous TiO2 films loaded with silver nanoparticles Appl. Phys. Lett. 99, 173106 (2011) Computational study on structural modification of single-walled carbon nanotubes by electron irradiation J. Appl. Phys. 109, 054304 (2011) Multiwalled carbon nanotubes and dispersed nanodiamond novel hybrids: Microscopic structure evolution, physical properties, and radiation resilience J. Appl. Phys. 109, 014314 (2011) Continuous-wave laser annealing of Si-ri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
128
2

Year Published

2004
2004
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(130 citation statements)
references
References 14 publications
0
128
2
Order By: Relevance
“…The efficiency of magnetic-dielectric absorbers is high because the complex permittivity (ε΄-jε˝) and permeability (µ΄-jµ˝) differ from zero [4][5][6]. In general, the suitable values of RAM can be achieved by adding lossy fillers and/or magnetic particles to a light weight that are physically and chemically stable one and of course have a high ability to absorb electromagnetic wave radiation [7][8][9][10]. The composite approach has been used to improve various material properties, including mechanical, chemical, structural, optical and electrical/magnetic etc [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of magnetic-dielectric absorbers is high because the complex permittivity (ε΄-jε˝) and permeability (µ΄-jµ˝) differ from zero [4][5][6]. In general, the suitable values of RAM can be achieved by adding lossy fillers and/or magnetic particles to a light weight that are physically and chemically stable one and of course have a high ability to absorb electromagnetic wave radiation [7][8][9][10]. The composite approach has been used to improve various material properties, including mechanical, chemical, structural, optical and electrical/magnetic etc [11][12][13][14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…During the MW irradiation process dipoles formed on the nanotube surface and interstitial channels interact with the microwave field leading to some absorption, which is lost through heating [9]. The activation of carbon nanotubes (CNTs) is due essentially to the "lightening rod" effect, and occurs when a metallic rod (e.g., a multi-walled CNT) is inserted into a region of a uniform electric field Eo.…”
Section: Discussionmentioning
confidence: 99%
“…Even though these calculations are static, they apply to the microwave fields as well, because the plasma frequencies of both CNTs and gold nanoparticles are much higher (UV range) than the microwave frequencies [12]. Since dipoles both on the surface and interstitial channels of nanotubes are involved in the activation of single wall CNTs [9], the interfacial mechanism for CNT-cell targeting was investigated. In this study, we observed that CNTs under MW exposure can target bacterial cells.…”
Section: Discussionmentioning
confidence: 99%
“…According to this mechanism, microwaves do not heat the material immediately; rather motion of the electrons is induced by electric field, causing sample heating. In this way, Joule heating induced by the metal catalyst particles should generate localized superheating (Wadhawan, Garrett, and Perez 2003). The behavior of amorphous carbon and graphite impurities under the microwave irradiation is less controversial; extended π-system permits conductivity (and thus joule heating) to enable localized heating.…”
Section: Mechanism Of the Carbon Nanotube-microwave Interactionmentioning
confidence: 99%